Kontribusi Power Otot Lengan dan Koordinasi Mata dan Tangan Terhadap Servis Atas Bola Voli Siswa Ekstrakurikuler SMAN 1 XIII Koto Kampar - Al Farisi, M Yendri; Daharis, Daharis (ANTHOR: Education and Learning Journal, 2023)
The purpose of this research was to determine the contribution of arm muscle power and hand-eye coordination to the volleyball extracurricular serve of SMAN 1 XIII Koto Kampar. The type of this research is multiple correlations. The sample in this study was 28 extracurricular students at SMAN 1 XIII Koto Kampar. The research instruments used were the overhead medicine ball throw test, the hand-eye coordination test and the volleyball serve test. The data analysis technique used is to calculate the contributionvalue from the multiple correlation values. Based on the results of data analysis it is known that (1) there is a contribution of arm muscle power to the volleyball service for extracurricular students at SMAN 1 XIII Koto Kampar by 25.30% with r.count = 0.503 > r.table = 0.374, (2) there is a contribution to the eye and hand coordination on the volleyball extracurricular service for SMAN 1 XIII Koto Kampar students by 18.66% with r.count = 0.432 > r.table = 0.374, (3) There is a contribution of arm muscle power and eye and hand coordination to the volleyball service for extracurricular students at SMAN 1 XIII Koto Kampar is 33.99% with r.count = 0.583 > r.table = 0.374.